POSMEDIA: A Conceptual Model for Digital Health Promotion and Posyandu Cadre Empowerment Using ToC - Afriza Dwi Islami Putra (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Maternal and child health remains a crucial indicator of national welfare, yet promotional efforts at the community level are often hindered by limited digital literacy among posyandu cadres. Despite the growing role of social media as an effective channel for health communication, most cadres lack the skills to produce and disseminate engaging educational content. Objective : This conceptual paper aims to propose POSMEDIA (Posyandu Melek Media) as an innovative model for enhancing the digital capacity of posyandu cadres through social media-based health promotion using the Theory of Change (ToC) framework. Research Methods/ Implementation Methods : This study adopts a conceptual design by integrating the Theory of Change and the ADDIE instructional development model (Analysis, Design, Development, Implementation, Evaluation). The model emphasizes a systematic and measurable process to improve cadres’ digital competence and community engagement in maternal and child health promotion. Results : The conceptual framework of POSMEDIA outlines a logical progression from digital literacy enhancement to sustainable social transformation. The model identifies key stages capacity building, content creation, social media engagement, and behavioral outcomes leading to a measurable increase in health communication effectiveness at the community level. Conclusion/Lesson Learned : POSMEDIA provides a theoretically grounded and adaptable framework for empowering posyandu cadres as digital health educators. It contributes to both academic discourse and practical implementation of health communication strategies, supporting the transformation of posyandu into digital-based community health information centers.